Pulsed laser generation in S+/S band using thulium fluoride fiber with saturable absorber / Siti Aisyah Reduan - Siti Aisyah , Reduan (2020)
Demands on photonic applications has become highly saturated in C-band and L-band region, forcing the needs to work in S band region for the development of alternative data network and photonics technology tools to fulfill the future needs. There are only a few reports on exploiting S band fiber laser operation which mainly used depressed-cladding erbium-doped fiber (DC-EDF) as gain medium. The region covers only ~1480 nm to 1510 nm as mentioned by previous works. Other than that, there is limitation in the selection of rare-element gain medium to generate the emission in S band region. The use of thulium-fluoride fiber (TFF) as gain medium has been focusing in S band fiber laser since it allows the laser amplification that covers a shorter wavelength in S band region. Besides that, the ability of TFF to generate emission in S band region by a single up-conversion pumping which is a simpler and more cost-effective way, is seen to be the advantages compared to the other pumping scheme. The aim of this study is to investigate the generation of S+/S band fiber laser by using Thulium-Fluoride Fiber as a gain medium purposefully for photonics applications. Besides the investigation on TFF fiber laser in S band region, the gain profile will be calculated to identify the amplification of the proposed fiber laser. The tunability of the TFF laser will be studied by integrating the tunable band-pass filter (TBPF) into the cavity and precisely identifying the wavelength range that can be tuned. The accessibility of the generated laser in S band region for photonics applications will be identified. Saturable absorber (SA) is inserting into the cavity to investigate the generation of pulsed laser which are Q-switching and mode-locking, in S band region. Preparations and characterization of the SA will be done to identify the properties of the SA. The generation of dual-wavelength, Q-switched laser in the proposed experiment will be investigated by inserting an SA and Photonic crystal fiber (PCF) into the cavity. PCF is the potential optical media that will be used to study the generation of dual-wavelength laser in the proposed experiment. The studies commenced and the results obtained in this study can contribute to expanding telecommunication operation band and availability of photonics applications in shorter wavelength of S+/S band region.